2021
DOI: 10.1186/s12864-021-07549-7
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative genome analyses of four rice-infecting Rhizoctonia solani isolates reveal extensive enrichment of homogalacturonan modification genes

Abstract: Background Plant pathogenic isolates of Rhizoctonia solani anastomosis group 1-intraspecific group IA (AG1-IA) infect a wide range of crops causing diseases such as rice sheath blight (ShB). ShB has become a serious disease in rice production worldwide. Additional genome sequences of the rice-infecting R. solani isolates from different geographical regions will facilitate the identification of important pathogenicity-related genes in the fungus. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 112 publications
2
27
0
Order By: Relevance
“…Further, to determine the period of divergence of different AGs of R. solani we plotted the rate of synonymous substitution per synonymous site (Ks) between the orthogroups in the syntenic blocks between AG1-IA and the other sequenced AGs against the percentage of orthologous pairs. We considered the average rate in change of Ks value as 1.3x10 - 8 per year, as reported earlier in case of fungi. The maximum likelihood-based phylogenetic tree constructed using the single-copy orthogroups expectedly predicted AG1-IA and AG1-IB to be phylogenetically closest and they seems to have diverged around 28 million years ago (mya).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, to determine the period of divergence of different AGs of R. solani we plotted the rate of synonymous substitution per synonymous site (Ks) between the orthogroups in the syntenic blocks between AG1-IA and the other sequenced AGs against the percentage of orthologous pairs. We considered the average rate in change of Ks value as 1.3x10 - 8 per year, as reported earlier in case of fungi. The maximum likelihood-based phylogenetic tree constructed using the single-copy orthogroups expectedly predicted AG1-IA and AG1-IB to be phylogenetically closest and they seems to have diverged around 28 million years ago (mya).…”
Section: Resultsmentioning
confidence: 99%
“…This has been proposed to cause diversification of host range and increasing virulence. Previous genome based studies had revealed expansion/emergance of gene families/orthogoups in different AGs of R. solani 8, 14 . We have observed similar expansion of gene families in AG1-IA in comparison to its closest relative AG1-IB especially, the genes located in the duplicated gene blocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA-Seq reads were assembled as follows: Trinity --seqType fq --left reads_1.fq --right reads_2.fq --CPU 10 --max_memory 30G. Besides, the protein sequence, genomic sequence, and GFF file of R. solani AG1, AG3, AG4, AG5, AG6, and AG8 have all been released in 2021 [ 34 - 37 ] and downloaded from https://api.ncbi.nlm.nih.gov/datasets/v1alpha/genome/download .…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, R. solani pathogenesis has been studied at the genomic and transcriptomic level, including AG1-IA that causes sheath blight in rice ( Oryza sativa ), corn ( Zea mays ), and soybeans ( Gl ycine max; Zheng et al, 2013 ; Nadarajah et al, 2017 ; Xia et al, 2017 ; Yamamoto et al, 2019 ; Lee et al, 2021 ; Li et al, 2021a ), AG1-IB that infects lettuce ( Wibberg et al, 2015 ; Verwaaijen et al, 2017 ), AG3 that infects potatoes ( Cubeta et al, 2014 ; Patil et al, 2018 ; Zrenner et al, 2020 ), and AG8 that infects wheat ( Hane et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%